Analisis Pendapatan dan Nilai Ekonomi Wisata Alam Taman Langit Pangalengan 360˚ - Sasongko, Dwi Agus (Pangale Journal of Forestry and Environment, 2023)
The COVID-19 pandemic caused a sharp decline in state revenue in the tourism sector in 2020, even though a year earlier tourism reached its peak as Indonesia’s largest foreign exchange earning sector with a value of USD 20 billion or the equivalent of Rp. 280 trillion. However, this condition slowly began to change as cases of COVID-19 began to decline. The Pangalengan 360˚ Sky Park Natural Tourism is one of the tourist attractions in Bandung Regency which began to grow in December 2020. Against the background of previously abandoned land, it is important to know how the management of nature tourism can provide income for the community and the amount of economic value for tourism. The purpose of this study was to determine tourist perceptions, tourism management income, and calculate the economic value of nature tourism. The research was conducted using the Travel Cost Method. This approach calculates the amount of travel costs incurred by tourists in order to enjoy The Pangalengan 360˚ Sky Park Natural Tourism. The conclusion of the study shows that The Pangalengan 360˚ Sky Park Natural Tourism gets very good perceptions from tourists; the gross income of the manager of the Pangalengan 360˚ Sky Park is Rp. 4,632,025,200/year; as well as the economic value of Pangalengan 360˚ Sky Park is Rp. 46,358,040,000/year.